External Brain Tamponade Paradoxically Induced by Cerebrospinal Fluid Hypovolemia After Decompressive Craniectomy: A Retrospective Cohort Study. Issue 1 (19th January 2021) - Motoyama, Yasushi; Kogeichi, Yohei; Matsuoka, Ryuta; Takamura, Yoshiaki; Takeshima, Yasuhiro; Matsuda, Ryosuke; Tamura, Kentaro; Nishimura, Fumihiko; Yamada, Shuichi; Nakagawa, Ichiro; Saito, Kozue; Park, Young-Su; et al.
ABSTRACT: BACKGROUND: Symptomatic hygroma after decompressive craniectomy (DC) presenting with a mass effect has been reported as external brain tamponade (EBT). However, the pathology of EBT is unclear. OBJECTIVE: To survey the clinical characteristics and explore the potential causes of EBT. METHODS: The incidence, timing of onset, and symptoms of EBT were examined among 155 patients undergoing supratentorial DC at Nara Medical University. The factors associated with EBT were investigated and compared with those with hygroma to estimate the potentially causative mechanisms. RESULTS: We identified 81 hygromas within 30 d after DC. Among them, 10 patients had EBT, including 7 with aneurysmal subarachnoid hemorrhage (aSAH), 2 with traumatic head injury accompanying skull base fracture, and 1 with a brain tumor. The median interval between DC and EBT was 3.5 d (range 1-21 d). Altered mental status was observed in 9, and oculomotor palsy was present in 3 patients. Univariate analysis demonstrated that risk factors for EBT were aSAH ( P  = .02) and lumbar spinal drainage (LSD; P  < .001). On the other hand, independent risk factors for hygroma included aSAH (odds ratio [OR]: 3.67, 95% confidence interval [CI]: 1.45-9.3, P  < .01) and ventricular drainage (OR: .14, 95% CI: .03-.802, P  = .03). CONCLUSION: Cerebrospinal fluid (CSF) hypovolemia after DC should be considered a potential cause of EBT, which includes brain herniation into the hiatus centralis and paradoxical formation of a hygroma. Correction of CSF dynamics and cranioplasty may be effective treatments for EBT.